Functional characterization of sequence variants in leucine-rich repeat kinase 2 (LRRK2) and its possible interaction with the translocase of outer mitochondrial membrane (TOM) protein complex - Neethling, Annika (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.